German Registry for Acute Aortic Dissection Type A (GERAADA): new software design, parameters and their definitions - Weigang, Ernst; Görgen, C.; Kallenbach, Klaus; Dapunt, O.; Karck, Matthias (The thoracic and cardiovascular surgeon, 2011)
Thieme E-Books & E-Journals